Women and Violence In Hibualamo Traditions (An Analysis of Restorative Justice in Resolving Casses of Domestic Violence) - Apituley, Lilian Gressthy Florencya; Eddyono, Sri Wiyanti (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Cases of domestic violence are increasing in Indonesia, this is a manifestation of the unequal power relations between men and women and is also influenced by the culture/customs of the community, one of which is the Tobelo woman in the Hibualamo customs.Purposes of the Research: This study aims to explain the concept of Restorative Justice in the Indonesian criminal law system and the Restorative Justice Model in Resolving Domestic Violence Cases against Tobelo women.Methods of the Research: The research method used is a combination of empirical-normative legal research. The approach uses a socio-legal approach (social science) and a statutory approach (statute approach).Results of the Research: The results of this study include: 1. There is negative labeling of women in Tobelo customary law in the misunderstanding of the Hibualamo concept; 2. The concept of Restorative justice based on Hibualamo ideology which contains noble values that are fair and moral can be the basis for resolving cases of domestic violence in Tobelo to create harmonization and prevent multi-interpretation gaps in the implementation of restorative justice